TATA NIAGA GULA RAFINASI DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Agus Dwi Nugroho; Alia Bihrajihant Raya; Paksi Mei Penggalih; Sylvatra Puspita; Arif Wahyu Widada; Nur Chasanah; Wahyu Azis Nugroho; Abi Pratiwa Siregar (Universitas Muhammadiyah Purwokerto, 2019)
The distribution of refined sugar (RS) for small and medium industries (SMI) of the food has suffered a lot of misappropriation. To overcome it, the government will implement the auction system. The purposes of this research are 1) to identify conditions and problems the distribution of RS for SMI of food; 2) to know the readiness of SMI of food in facing RS auction system; and 3) to provide recommendations for improvement of the RS auction system. This research was conducted in Yogyakarta Province on November 2017. Research respondents are Industry and Trade Offices in DIY, food association, SMI of food and RS distributors. The problems in the distribution of RS are SMI didn’t know about the rules of RS distribution, the distribution of RS is not according to government regulations and the food association was unable to accommodate the trade of RS. SMI hasn’t been able to participate in the auction system so it needs 1) the government conducts of socialization and supervision of the RS trading system; 2) SMI establishes business units and obtain capital facilitations and 3) the government gives authorizes for BULOG to distribute RS.